Institutionalization of innovations in the context of strengthening economic security of a state and enterprises - Brytskyi, R. M. (Видавництво Львівської політехніки, 2014)
The description of factors that determine the characteristics of the institutional environment is given in the article. The necessity of a more in-depth study of the problems associated with institutionalization of innovation in the context of strengthening the economic security of all market participants and improving management capitalization economy is proved. Attention is focused on strengthening the processes of institutionalization of innovation in terms of exacerbation of systemic crisis in Ukraine. Подано характеристику факторів, що визначають особливості розвитку інституційного середовища. Доведено необхідність глибиннішого дослідження проблем, які пов’язані з інституціоналізацією інновацій, у контексті зміцнення економічної безпеки всіх учасників ринку і покращення процесів управління капіталізацією економіки. Акцентовано увагу на посиленні процесів інституціоналізації інновацій в умовах загострення системної кризи в Україні.
Інституціоналізація інновацій у контексті зміцнення економічної безпеки держави та підприємств
Keywords: institutionalization; institutionalization of innovations; capitalization; economic security; інституціоналізація; інституціоналізація інновацій; капіталізація; економічна безпека